Novel Reconnection-Less Reconfigurable Filter Design Based on Unknown Nodal Voltages Method and Its Fractional-Order Counterpart - Langhammer, Lukas; Sotner, Roman; Dvorak, Jan; Jerabek, Jan; Ushakov, Peter A. (Elektronika ir Elektrotechnika, 2019)
A novel solution of reconnection-less electronically reconfigurable filter is introduced in the paper. The filter is designed based on unknown nodal voltages method (MUNV) using operational transconductance amplifiers (OTAs) and variable gain amplifier (VGA). The structure can provide all-pass, band-stop, high-pass 2nd order functions, high-pass function of the 1st order and direct transfer from the same topology without requirement of manual reconnection. The proposed structure also offers the electronic control of the pole frequency. Moreover, fractional-order design of the proposed filter is also provided. The behaviour is verified by simulations using Cadence IC6 (spectre) software.